Laccase‐containing ureasil–polymer composite as the sensing layer of an amperometric biosensor. Issue 36 (19th May 2017) - Kavetskyy, Taras; Smutok, Oleh; Gonchar, Mykhailo; Demkiv, Olha; Klepach, Halyna; Kukhazh, Yuliia; Šauša, Ondrej; Petkova, Tamara; Boev, Victor; Ilcheva, Vania; Petkov, Plamen; Stepanov, Andrey L.
ABSTRACT: Innovative amperometric biosensors for monitoring the level of wastewater pollution have been constructed on the surface of the gold planar electrodes C220AT "DropSens" by using the organic–inorganic ureasil‐based composites as host matrixes and immobilized commercial laccase from Trametes versicolor . It was found that the biosensor based on the ureasil–chalcogenide glass composite is characterized by a very high sensitivity (67, 540 А M −1 m −2 ) that is 38.3 times higher than for pure ureasil (the sensitivity of the bioelectrode was calculated as 1762 А M −1 m −2 ). On the other hand, application of the ureasil–chalcogenide glass composite with incorporated silver nanoparticles (NPs) synthesized by high‐dose (1.0 × 10 17 Ag + /cm 2 ) 30 keV Ag + ion implantation results in decreasing the biosensor sensitivity up to 2390 times (the sensitivity of the bioelectrode was 28.3 А M −1 m −2 ). The role of additives (chalcogenide glass and silver NPs) in the ureasil matrix on the biofunctionality of the biosensors produced is considered. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45278. Abstract :